Development and applications of the SWAN rating scale for assessment of attention deficit hyperactivity disorder: a literature review - Azoni, Cíntia Alves Salgado (2015)
This study reviewed the use of the Strengths and Weaknesses of Attention-Deficit/Hyperactivity-symptoms and Normal-behaviors (SWAN) rating scale in diagnostic and evolutive approaches to attention deficit hyperactivity disorder (ADHD) and in correlational studies of the disorder. A review of articles published in indexed journals from electronic databases was conducted and 61 articles on the SWAN scale were analyzed. From these, 27 were selected to a) examine use of SWAN in research on attention disorders and b) verify evidence of its usefulness in the areas of genetics, neuropsychology, diagnostics, psychiatric comorbidities, neuroimaging, pharmacotherapy, and to examine its statistical reliability and validity in studies of diverse populations. This review of articles indicated a growing use of the SWAN scale for diagnostic purposes, for therapy, and in research on areas other than ADHD, especially when compared with other reliable scales. Use of the scale in ADHD diagnosis requires further statistical testing to define its psychometric properties.